1995 Proceedings. 45th Electronic Components and Technology Conference
DOI: 10.1109/ectc.1995.515335
|View full text |Cite
|
Sign up to set email alerts
|

Copper-diamond composite substrates for electronic components

Abstract: Be0 AINThe application of high power density electronic components such as fast microprocessors and power semiconductors is often limited by an inability to maintain the device junctions below their maximum rated operaring temperature. The junction temperature rise is determined by the t h d resistance from junction to the ambient thermal environmeat Two of the largest contributions to this thermal resistance are the die attach interface and the package base. A decrease in these resistances can allow increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Some researches describe the approaches to improve the interface bonding between the matrix and the filler that have a multi-layered coating [21][22][23]. In this work, dual-layer coatings on the diamond particles are designed to produce the diamond/Cu composites with desirable thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some researches describe the approaches to improve the interface bonding between the matrix and the filler that have a multi-layered coating [21][22][23]. In this work, dual-layer coatings on the diamond particles are designed to produce the diamond/Cu composites with desirable thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The grains are entrapped inside the copper, but not bound to it, and that the copper coating has a thickness of several microns. Previously, Davidson et al [5] successfully used industrial powder to make composites and discovered that by filling a mould with the powder and mechanically pecking it, the powder can easily be moulded into the desired shape. The initial filling thickness of commercial diamond powder, as well as the pressure required to compact the preform, have been determined experimentally.…”
Section: 2liquid Metal Infiltrationmentioning
confidence: 99%
“…Loutfy et al developed advanced diamond-based metal matrix composites for thermal management of RF devices with a TEC of 7:5ðppm=KÞ and a thermal conductivity of 500ðW=m-KÞ [79]. Davidson et al used copper-diamond composite substrates for electronic components with a thermal conductivity of 420ðW=m-KÞ [80]. Faqir et al reported a novel packaging solution for GaN power electronics using silver-diamond composite package with a TEC matching that of the semiconductor material and a thermal conductivity as high as 700ðW=m-KÞ, which is significantly larger than that of CuW [81].…”
Section: Thermal Management Solutions For Power Electronicsmentioning
confidence: 99%